Speed Control of PWM Inverter fed Induction Motor: An ANN and Vector Control Based Approach - Rehana Perveen, S.K. Sinha, Ajay Shekhar Pandey (International Journal of Advanced Science and Technology, 2020)
This paper presents a comparative study of artificial neural networks (ANN) over conventional vector controllers with pulse width modulation inverter fed induction motor. The ANN control system implemented here is based on a nonlinear autoregressive moving average (NARMAL2) algorithm. The accuracy of the flux calculation is done by adjusting the training data offline with new weights. Subsequently different cases are simulated with Matlab/Simulink platform taking different motor load torque generating optimum value and steady sp